Perception of Academic Staff on Public-Private Partnership and Finance of Public University Education in Rivers State - Woyengikuro , Kolubowei (International Journal of Educational Management, 2025)
The study is on perception of academic staff on public-private partnership and finance of public university education in Rivers State. Three (3) research questions and three (3) null hypotheses guided the study. The design of the study was descriptive survey design. The population of the study was 2619 lecturers and a sample of347 which is 13% of the entire population of the study. The instrument for data collection was a self-designed questionnaire captioned "Academic Staff on Public-Private Partnership Questionnaire (ASPPPQ) which was content and face validated with a reliability coefficient of 0.82. Mean score and standard deviation was used to answer the research questions and z-test was used to analyze the null hypotheses. It was discovered that the private sector can finance university education when they design, build, and operate universities and concluded that public private partnership is critical in financing university education and hence, recommended that Government and institutional leaders should find out ways of ensuring public private partnership financing in public universities in Rivers State. for instance, government can cooperates with educational institutions to deliver unique services, the government can connect with private enterprises in order to protect current infrastructures, in various fields, higher institutions are expected to build, develop and maintain good ties with private businesses.